Religious Understanding of Online Loan Consequences and Usury (Riba) in Educational Financing Decisions - Moh Wardi; Farihatul Hasanah; Sri Irawati; Hodairiyah Hodairiyah (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
The rising cost of education has prompted students and families to seek alternative financing, including online loans. However, the use of online loans for education financing raises ethical and religious issues, particularly related to the practice of usury, which is expressly prohibited in Islamic teachings. This study aims to analyze the influence of religious understanding regarding the consequences of online loans and usury on individuals' decisions to use online loans as a source of education financing. This study used a mixed methods approach. Quantitative data were collected through a structured questionnaire from 20 respondents who had experience or considered using online loans for education, while qualitative data were obtained through in-depth interviews with 7 religious and community leaders regarding the concept, understanding, and impact of online loans on education financing. Quantitative data were analyzed using descriptive statistics and regression analysis to identify the relationship between religious understanding, awareness of loan consequences, and the decision to borrow for education financing. The analysis results showed that the variables of understanding online loans (X1) and understanding of religious values ​​(X2) did not have a significant influence on the decision to take out online loans for education financing (Y). Meanwhile, qualitative data were analyzed thematically to provide contextual and normative explanations for the quantitative findings. The results show that a higher level of religious understanding regarding usury and the socio-economic impacts of online loans significantly reduces individuals' likelihood of choosing online loans to finance education. Qualitative findings confirm that moral considerations, concerns about debt dependence, and a commitment to Islamic financial ethics are key factors in financial decision-making. This research contributes to the development of faith-based financial behavior studies and emphasizes the importance of religious literacy in addressing the challenges of education financing in the digital era.